Gene family evolution and natural selection signatures in Datura spp. (Solanaceae) - De-la-Cruz, Ivan M.; Kariñho-Betancourt, Eunice; Núñez-Farfán, Juan; Oyama, Ken (Frontiers in Ecology and Evolution, 2022)
Elucidating the diversification process of congeneric species makes it necessary to identify the factors promoting species variation and diversification. Comparative gene family analysis allows us to elucidate the evolutionary history of species by identifying common genetic/genomic mechanisms underlying species responses to biotic and abiotic environments at the genomic level. In this study, we analyzed the high-quality transcriptomes of four Datura species, D. inoxia, D. pruinosa, D. stramonium and D. wrightii. We performed a thorough comparative gene family analysis to infer the role of selection in molecular variation, changes in protein physicochemical properties, and gain/loss of genes during their diversification processes. The results revealed common and species-specific signals of positive selection, physicochemical divergence and/or expansion of metabolic genes (e.g., transferases and oxidoreductases) associated with terpene and tropane metabolism and some resistance genes (R genes). The gene family analysis presented here is a valuable tool for understanding the genome evolution of economically and ecologically significant taxa such as the Solanaceae family.